EMPOWERING VOICES: HOW DIGITAL MEDIA IS REVOLUTIONIZING FEMINIST WRITING - Melania Priska Mendrofa (Linguistics and Literature Students' Journal, 2023)
In the modern world, technology plays a vital role in shaping society. It has become an inseparable part of our lives, revolutionizing various aspects such as communication and entertainment. This article explores how digital media technology is transforming feminist writing and empowering women's voices. By utilizing platforms like websites, blogs, and eBooks, women can amplify their thoughts and bridge existing gaps within the literary world. The implementation of AI algorithms enables the analysis of vast literary works, bringing attention to previously overlooked patterns and biases. This contributes to a more inclusive and diverse literary landscape. The article applies the Neoliberal Feminism concept by Catherine Rottenberg, emphasizing individuals as active participants who can stimulate the economy by regulating government operations. The free and self-regulating market facilitated by digital media empowers women to change their marginal situations. In summary, this article promotes digital media as a potential technology for leveling the playing field for female writers. It enables women's voices to be heard and acknowledged and opens avenues for valuable feedback, guidance, and exposure. This empowerment paves the way for greater representation of women in literature.Keywords: digital media, feminist writing, neoliberal feminism